Peer review of the pesticide risk assessment of the active substance benfluralin. (15th November 2019) - ,; Arena, Maria; Auteri, Domenica; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Norway, and co‐rapporteur Member State, the Netherlands, for the pesticide active substance benfluralin are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of benfluralin as a herbicide on chicory and lettuce. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.